Handheld vibration effects shoulder motion - Tripp, B. L.; Eberman, L. E.; Dwelly, P. M. (International Journal of Sports Medicine, 2009)
We explored effects of handheld vibration on glenohumeral motion in competitive overhead-throwing athletes. We used a randomized, blinded pre-test post-test cross-over design. Each arm of each subject experienced 2 conditions (1-control, 1-experimental), each with pre-test and post-test measures; the order of which was randomized. Participants included Division-I baseball and softball players (n=35: age=20±2 yr, height=178±9 cm, mass=84±12 kg, years of sport participation=13±4 yrs). During the experimental condition, participants held a vibrating (2.2 mm, 15 Hz, 20 s), 2.55 kg (5.62 lbs) Mini-VibraFlex dumbbell (Orthometric, New York, NY) in neutral glenohumeral rotation. During the control condition, participants held the still dumbbell (0 mm, 0 Hz, 20 s). Participants rested one min after each trial (3). We used a digital protractor to assess range of motion bilaterally, employing a standard technique for measuring maximal internal (IR) and external rotation (ER). Repeated-measures analyses of variance indicated that range of dominant IR increased 6.8% (p=0.001, ES=0.16) after handheld vibration. Handheld vibration did not affect range of dominant ER (p>0.05, 1-ß=0.20), non-dominant IR (p>0.05, 1-ß=0.41), or non-dominant ER (p>0.05, 1-ß=0.05). Short bouts of handheld vibration increased dominant IR in collegiate baseball and softball athletes. These results suggest that handheld vibration may help maintain glenohumeral IR that is vital to the healthy and competitive throwing shoulder.